Adaptasi Fisiologis Dan Tingkah Laku Organisme Akuatik Terhadap Perubahan Salinitas - Astuti, Rika; Marlian, Neneng; Lubis, Friyuanita; Putri, Levi Rianti; Haikal, Muhammad; Nufus, Hayatun (Universitas Teuku Umar, 2024)
The ability to adaptation and change the behavior of fish is a physiological response that occurs naturally in fish in waters which is strongly influenced by aquatic environmental factors. This research aimed to the test of adaptability and behavioral changed of fish as a resulted of physiological responsed to the changed in salinity. This research was carried out in March 2023 at the Environmental Productivity Laboratory, Faculty of Fisheries and Marine Sciences, Teuku Umar University. The research procedure was carried out by inserting 5 test animals (catfish and goldfish) into an aquarium filled with 10 liters of water. Table salt was added to each aquarium with salinity treatment, namely 5 ppt and 10 ppt gradually over 7 days. Based on the research resulted, it showed that catfish and goldfish had different responses to physiological and behavioral adaptations with different salinity treatments (5 ppt and 10 ppt). Giving 5 ppt salinity to the test animals (catfish and goldfish) the operculum movement at 20 minutes still looked normal, the operculum movement began to slowed down as time increasing to 25 minutes and further slowed down at 30 minutes. Treated with 10 ppt salinity in the test animals ( catfish and goldfish) showed unusual changes in physiological behavior with high leveled of stress. In the 5 ppt and 10 ppt treated with added salinity on the second to seventh day the catfish experienced mortality with a survival rated of 60%, while in the 5 ppt and 10 ppt treated with added salinity the goldfish on the first to the seventh day experienced mortality with a survival rated of 0%.